Logistics network configuration for seasonal perishable food supply chains - Javier Arturo Orjuela Castro; Juan Pablo Orejuela-Cabrera; Wilson Adarme-Jaimes (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The location of actors and production, transformation, commercialization and distribution facilities generate the configuration of the perishable food supply chain (PFSC). The logistics network design (LND) lead to different supply, storage and distribution environments and result in flows, these logistics operations have an impact on the performance of the chain of fresh agricultural products. Specifically, in the PFSC with seasonality, a temporary imbalance between supply and demand is generated, which affects the balance in the flows and affects the losses, costs and response capacity. This research study that problem. Design/methodology/approach: A multi-echelon, multi-objective and multi-product model is established that determines the configuration of the logistics network of the PFSC with seasonally and allows actors to approach efficiency frontiers, which contribute to their permanence in the markets. The model was applied to the case of the perishable fruit supply chain, in a developing country, Colombia. The population information was taken from government surveys and studies, which allowed parameterizing the model. Findings: The application of model permitted to answer the next questions: How does improve the performance from PFSC through logistics network design? And, How the existence of smallholdings in food production and from retail merchants is preserved? In the perishable food supply chain. Social implications: Where the perishable food supply chain actors are located in non-efficient borders and their sustainability may be affected by competition factors, the stakeholders should focus on increasing food availability and reducing losses to improve access and therefore food security. Originality/value: A new model for the logistics network configurations of seasonal perishable fruit supply chain was development, the optimizing from five objectives with two sub-models is obtained, one for surplus and the other for the deficit moments. The model includes real conditions, such as, fruit loss due T0 and RH by different thermal floors and the means used for the transport of fruits in mountain areas at countries in route of development. The impact over the small producers, retailers and consumers in the times of scarcity or surplus was analyzed.
Keywords: 650